Skin graft of contralateral aesthetic unit for reconstruction of the upper eyelid: case report and literature review - Llave, Heriberto Garza de la; Orozco-Grados, Jose de Jesus; Rodriguez, Carlos Eduardo; Chavez-Serna, Enrique (International Journal of Research in Medical Sciences, 2021)
Eyelids represent a complex structure; its principal function is to provide physical and immunological barrier. The complexity of this structure lies in the blinking and in the range of movement they carry out respecting the integrity of the cornea. The objective of this study is to provide a surgical alternative with minimal morbidity for the reconstruction of the upper eyelid, as well as to present the available tools for the treatment of this complex area of the facial anatomy. We present the case of a female patient of 62 years, with 50% of necrosis on the surface of the upper eyelid and infection data, surgical management was initiated with debridement, systemic antibiotic therapy and negative pressure system device, once the infectious process was resolved and according to the principles of reconstruction by aesthetic subunits, it was decided to reconstruct 100% of the subunit affected by a skin graft of total thickness of the contralateral eyelid through a blepharoplasty with good aesthetic-functional results. The reconstruction of the eyelids should be managed by a plastic surgeon, taking into account the principles of the aesthetic subunits, optimally the donor tissue should have similarity with the tissue to be reconstructed, with respect to the size, color and flexibility, to obtain an adequate aesthetic and functional result.